CONIFEROUS WOODS IN THE EARLY PLEISTOCENE BROWN COALS OF THE LEFFE BASIN (LOMBARDY, ITALY). Ecological and biostratigraphic inferences (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
49 autochthonous wood samples collected in brown coal from the Leffe palustrine deposits (Early Pleistocene, Lombardy, N-Italy) have been identified and their stratigraphical position has been discussed in comparison with pollen spectra. A peat level in the lower part of the succession contains Piceoxylon wood. Pollen spectra point to a conifer forest of dry and cool climate. Glyptostroboxylon  tenerum,  Chamaecyparis, Pinus aff. tabulaeformis, Carya, Pterocarya, Alnus, Fraxinus and Celtis woods have been identified from the "Main" brown coal layer in the middle (biogenic) unit of the Leffe Formation. The coniferous woods are described and some inferences about their ecological requirements are presented. These trees formed part of the swamp vegetation during interglacial phases. Pinus occurred, only during meso/oligotrophic phases. The biostratigraphic interest of these finds and climate dynamics are discussed, in order to interpret the discontinuous record of the "Tertiary plants" in Northern Italy during lowermost Pleistocene.
Keywords: Coniferous woods; Early Pleistocene; Leffe Basin; Lombardy; Italy.